A Guide to Greenhouse Gas Benchmarking for Climate Policy Instruments - Partnership for Market Readiness (World Bank, Washington, DC, 2017)
The past year has seen a significant increase in global momentum for climate action. As of April 2017, one hundred thirty-seven Parties to the United Nations Framework Convention on Climate Change (UNFCCC) have already submitted their first nationally determined contributions (NDCs) as part of their commitments to the Paris Climate Agreement. Climate policy instruments are increasingly being used or considered by countries to contribute to mitigation commitments. Benchmarks have been used in climate policy instruments to set targets and thresholds for environmental performance, and to determine the distribution of instrument benefits and obligations. Jurisdictions with mature ETSs, such as the European Union, New Zealand, Tokyo, and California, have been using benchmarks for allocation of emissions allowances in many or all of the sectors that are covered. In recent years, countries developing ETSs have also been exploring the use of benchmarks. This "Guide to Greenhouse Gas Benchmarking for Climate Policy Instruments" is intended to provide policymakers with structured guidance on the development of benchmarks and draws on over a decade of global experiences in benchmark development, covering practices in 16 jurisdictions that are already using or are in the process of developing a benchmarking approach.